Fate and Effects of Oil Pollutants in Extremely Cold Marine Environments. - Atlas,Ronald M (1979)
Studies were conducted on the fate and effects of crude and refined oils in Arctic ecosystems. Major conclusions of the stufy were: (1) Microbial populations respond rapidly to an introduction of hydrocarbons into the environment by an increase of the number of hydrocarbon utilizing bacteria and a decrease in species diversity; (2) Hydrocarbons will remain in Arctic ecosystems for prolonged periods following contamination. Following initial abiotic weathering, biodegradation occur slowly. The fate depends on the particular ecosystem that is contaminated. Refined oil spillages may contaminate drinking water supplies for long periods of time; (3) Hydrocarbon biodegradation in the Arctici is limited mainly by nitrogen and phosphorus, and to a lesser extent by low temperatures. Hydrocarbon utilizing microorganisms are widely distributed; (4) When crude oil is exposed on water, biodegradation reduces absolute amounts of petroleum hydrocarbons, but does not appear to alter the relative percentages of oil components. This appears to be a major difference between petroleum biodegradation in the Arctic and in temperate regions; and (5) Petroleum contamination of Arctic sediments will result in alterations of the benthic community. Petroleum exhibits differential toxicity to benthic invertebrates.